RF front end for 5.8GHz wireless LAN - Zhang, Ling (2008)
This project is to study and set up the transceiver RF front end for 5.8GHz U-NII band. This project will be limited to the search and selection of the suitable parts, setting up of the transceiver architecture, and evaluating the transceiver link performance using the Agilent Technology ADS simulators.